Laser forming and welding processes - Yilbas, Bekir Sami (Materials Forming, Machining and Tribology, 2013)
This book introduces model studies and experimental results associated with laser forming and welding such as laser induced bending, welding of sheet metals, and related practical applications. The book provides insight into the physical processes involved with laser forming and welding. The analytical study covers the formulation of laser induced bending while the model study demonstrates the simulation of bending and welding processes using the finite element method. Analytical and numerical solutions for laser forming and welding problems are provided.